ChemInform Abstract: Structures of Ryobunins A—C from the Leaves of Clethra barbinervis. Issue 43 (7th October 2013) - Sugimoto, Sachiko; Matsunami, Katsuyoshi; Otsuka, Hideaki
Abstract The new ursane‐type triterpene glucoside, ryobunin A (I), a seco‐ursane type triterpene glucoside, ryobunin B (II), and one oleanane type triterpene glucoside, ryobunin C (III), are isolated along with four known compounds.